Dirasah Ma Ba’da al-Waqi’ah Laday Thullab al-Shaf al-Tsanawiy ‘An Uslub al-Muhakah li Tarqiyyah Isti’ab al-Mufradat - Rozaanah, Rozaanah; Riyadi, Slamet; Fikri, Hidayatul (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2022)
The purpose of this study was to know the student's Arabic vocabulary mastery in the class that did not use simulation methods and classes that used simulation methods, and to what degree the effectiveness of the methods used to increase student's Arabic vocabulary mastery of the XI class in Pondok Pesantren Modern Ta 'dib al-Syakirin, Medan Johor. The research method used is an ex post facto quantitative study method. The results of this study indicate that for mastery of the student's Arabic vocabulary when not using the practice of simulation are obtained with an average of 64.72, where 4 students are "excellent", 2 people who are "good",7 people who are predicated "enough", and 5 people who are predicated "less". While the student's Arabic vocabulary mastery when using simulation methods is obtained with an average value of 83.61, which are 5 students on a "satisfactory" predicate, 10 on "excellent", 2 on a "good" predicate, and 1 person on a "less" predicate. As well as analysis of data, it has been found that the use of simulated methods is effective to increase student's Arabic vocabulary mastery with a level of effectiveness given by 0.54 based on n - gain tests by "moderate" since n-gain values are in the range of 0.30. < g < 0.70.